Successful management of refractory hyperammonemia in metastatic neuroendocrine tumor - Pande, Apurva; Philips, Cyriac Abby; Patidar, Yashwant (International Journal of Advances in Medicine, 2017)
Neuroendocrine tumors (NETs) form a heterogeneous group of neoplasms composed of pancreatic NETs and carcinoid tumors. Refractory hyper-ammonemia related encephalopathy is a condition seen rarely with metabolic liver disease and commonly with intra-abdominal shunts in the presence or absence of cirrhosis. We present here, a rare cause of medically refractory hyperammonemia, secondary to metastatic neuroendocrine tumor which was managed through interventional radiology measures. Apart from other causes of central nervous system involvement in metastatic neuroendocrine tumors, intratumoral microportovenous shunting and its management drastically improves outcomes and quality of life when diagnosed early.